f+13/4=4 solve for f

Answers

Answer 1

Answer:

f= .75 or 3/4

Step-by-step explanation:

13/4 = 3 1/4 or 3.25

4-3.25= .75

Or

3/4

Answer 2

Answer:

f = 3/4

Step-by-step explanation:

f+(13/4)= 4

subtract (13/4) from both sides

⇒f + (13/4)- (13/4) = 4 -(13/4)        

⇒f =(16-13) /4

∴f = 3/4


Related Questions

An app developer projects that he will earn 230$ for every 100 apps downloaded .which of the following equation can be used to be represented the proportional relationship between the number of apps ,x,and the total earnings
V

Answers

The developer would earn $50.00 if 20 apps are downloaded. Similarly, they can calculate earnings for any other number of app downloads using this equation.

To represent the proportional relationship between the total earnings (y) and the number of apps downloaded (x), we can use the formula for direct variation, which is:

[tex]\[ y = kx \][/tex]

Where:

- [tex]\( y \)[/tex] represents the total earnings,

- [tex]\( x \)[/tex] represents the number of apps downloaded, and

- [tex]\( k \)[/tex] is the constant of proportionality.

In this scenario, the app developer earns $20.00 for every 8 apps downloaded. This means that for every 8 apps downloaded, the earnings increase by $20.00. So, the constant of proportionality [tex](\( k \))[/tex] is the rate at which earnings increase per app downloaded.

To find the value of [tex]\( k \)[/tex], we can divide the total earnings by the number of apps downloaded:

[tex]\[ k = \frac{y}{x} \][/tex]

Given that the developer earns $20.00 for every 8 apps downloaded, we can substitute these values into the equation:

[tex]\[ k = \frac{20}{8} \][/tex]

[tex]\[ k = 2.5 \][/tex]

Now that we have the value of [tex]\( k \)[/tex], we can rewrite the equation with this value:

[tex]\[ y = 2.5x \][/tex]

This equation represents the proportional relationship between the total earnings [tex](\( y \))[/tex] and the number of apps downloaded [tex](\( x \))[/tex]. It shows that for every additional app downloaded, the total earnings increase by $2.50, maintaining a consistent rate of increase.

This equation allows the app developer to predict their earnings based on the number of apps downloaded. For example, if 20 apps are downloaded, the total earnings can be calculated as:

[tex]\[ y = 2.5 \times 20 = 50 \][/tex]

So, the developer would earn $50.00 if 20 apps are downloaded. Similarly, they can calculate earnings for any other number of app downloads using this equation.

Is -0.5 an integer? Explain.​

Answers

Yes, -0.5 is an integer because it is a negative number. Any number that is positive or negative is an integer.

Answer:  the explanation is given below. The number is NOT an integer.

Step-by-step explanation:  We are given to check whether the number -0.5 is an integer or not.

We know that

an integer is a number where the digits after the decimal are zero, or the denominator of its fractional form is 1.

The given number is

[tex]n=-0.5.[/tex]

Here, we can see that the digits after the decimal is 5, not zero. Also,  

this number can be represented as a negative fraction with denominator not equal to 1 is as follows :

[tex]n=-\dfrac{5}{10}=-\dfrac{1}{2}.[/tex]

Therefore, this number is NOT an integer.

PLEASE HELP!!!

-x/4 - 2 = x + 1​

Answers

Answer:

-x/4-3=x

Step-by-step explanation:

Answer:

-12/5

Step-by-step explanation:

-x/4-2=x+1

-x/4-x-2=1

-x/4-x=1+2

-x/4-x=3

-1/4x-4/4x=3

-5/4x=3

x=3/(-5/4)

x=(3/1)(-4/5)

x=-12/5

Solve m² + 8m = -3 by completing the square.
(Use a comma to separate multiple values.)



What the answer for this?

Answers

Answer:

Step-by-step explanation:

m² + 8m = -3

(m² + 8m+16) -16 = -3

(m+4)² = 13.....continue

Use the quadratic formula to find both solutions to the quadratic equation
given below.
3x^2 - 7x - 1 = 0


which answers (in da pic)
HELP A BROTHA OUT!!!

Answers

There you go! lmk if you have questions
Final answer:

The solutions to the quadratic equation 3x^2 - 7x - 1 = 0, using the quadratic formula, are x = [7 + sqrt(61)]/6 and x = [7 - sqrt(61)]/6.

Explanation:

This question pertains to the solving of a quadratic equation using the quadratic formula. The quadratic formula is given by x = [-b ± sqrt(b^2 - 4ac)]/2a. In equation 3x^2 - 7x - 1 = 0, comparing it with the standard form of quadratic equation ax^2 + bx + c = 0, we can assign: a = 3, b = -7, and c = -1. Substituting these values into the formula, we get: x = [7 ± sqrt((-7)^2 - 4*3*(-1))]/2*3 = [7 ± sqrt(49 + 12)]/6 = [7 ± sqrt(61)]/6. So, the solutions to the equation are x = [7 + sqrt(61)]/6 and x = [7 - sqrt(61)]/6.

Learn more about Quadratic Equation here:

https://brainly.com/question/30766352

#SPJ11

A rectangle has an area of 90 square centimeters and a height of 12.5 centimeters. What is the length of the base?

Answers

Answer: l = 7.2

Step-by-step explanation:

90/12.5 = 7.2

7.2 * 12.5 = 90

Answer:

length of the rectangle is 7.2 centimeters.

Step-by-step explanation:

Area of the rectangle has been given as 90 square centimeters.

Height of the rectangle = 12.5 centimeters

Now we have to calculate the length of the rectangle.

Since, Area of the rectangle = Length × height

90 = 12.5 × length

Length = [tex]\frac{90}{12.5}[/tex]

           = 7.2 centimeters

Therefore, length of the rectangle is 7.2 centimeters.

Which of the following fractions is equivalent to 4/20
A. 3/15
B. 2/12
C. 1/10
D. 3/19
Please answer QUICKLY.

Answers

The equivalent fraction of 4/20 is 3/15

3/15 is equivalent to 4/20

Help math question theres a graph

Answers

dang this is hard for me, let me think

A glazier is setting supports in parallel segments to prevent glass breakage during storms. What are the values of x and y? Justify your conclusions.

Answers

Answer:

m∠y=50°

m∠x=50°

Step-by-step explanation:

we know that

The angles in matching corners are called corresponding angles. When the two lines are parallel Corresponding Angles are equal

so

m∠y=50° -----> by corresponding angles

and

The angles that are formed on opposite sides of the transversal and inside the two lines are alternate interior angles. When the lines are parallel, the alternate interior angles are equal.

so

m∠x=m∠y -----> by alternate interior angles

so

m∠x=50°

therefore

m∠y=50°

m∠x=50°

Equivalent expression of 7 square root 5

Answers

Answer:19

Step-by-step explanation:

Subtract then add

Solve the inequality for v

56>8v

Answers

Answer: 2

Step-by-step explanation:

Answer:

7614

Step-by-step explanation:

remove all perfect squares from inside the square root
[tex] \sqrt{45} [/tex]

Answers

Answer:

3√5 or ≈6.7082

Step-by-step explanation:

1) √45

2) Factor out the perfect square: √3²×5

3) The root of a product is equal to the product of the roots of each factor: √3²√5

4) Reduce the index of the radical and exponent with 2: 3√5

5) Solution: 3√5 or ≈ 6.7082

after removing the perfect square factor from inside the square root of 45, we are left with 3√5.

To remove all perfect squares from inside the square root of √45, we need to factorize 45 and separate the perfect square factors.

The prime factorization of 45 is 3 × 3 × 5. Since 3 is repeated twice, it represents a perfect square factor.

We can rewrite the square root of 45 as the square root of (3 × 3 × 5). Using the property of square roots (√ab = √a × √b), we can simplify it as √(3 × 3) × √5.

The square root of 3 × 3 equals 3, so the expression simplifies to 3√5.

Therefore, after removing the perfect square factor from inside the square root of 45, we are left with 3√5.

Learn more about square root here

https://brainly.com/question/91924

#SPJ6

find the equation of the circle: y-intercepts 4 and –8, contain (–12, –8)

Answers

Answer:

[tex]\boxed{(x+6)^2+(y+2)^2=72}[/tex]

Step-by-step explanation:

The center-radius form of the circle equation is given by:

[tex](x-h)^2+(y-k)^2=r^2[/tex]

Here we know that the y-intercepts are:

[tex]y=4 \ and \ y=-8[/tex]

So:

[tex]\bullet \ If \ y=4, \ x=0 \\ \\ \\ (0-h)^2+(4-k)^2=r^2 \\ \\ \therefore \mathbf{(I)} \ h^2+16-8k+k^2=r^2 \\ \\ \\ \bullet \ If \ y=-8, \ x=0 \\ \\ \\ (0-h)^2+(-8-k)^2=r^2 \\ \\ \therefore \mathbf{(II)} \ h^2+64+16k+k^2=r^2 \\ \\ \\ \bullet \ If \ x=-12, \ y=-8 \\ \\ \\ (-12-h)^2+(-8-k)^2=r^2 \\ \\ \therefore 144+24h+h^2+64+16k+k^2=r^2 \\ \\ \therefore \mathbf{(III)} \ h^2+208+16k+24h+k^2=r^2[/tex]

So we have the following system of equations:

[tex]\left\{ \begin{array}{c}(I)\:h^{2}+16-8k+k^{2}=r^{2}\\(II)\:h^{2}+64+16k+k^{2}=r^{2}\\(III)\:h^{2}+208+16k+24h+k^{2}=r^{2}\end{array}\right.[/tex]

[tex]Subtract \ II \ from \ I \\ \\ \\\left\{ \begin{array}{c}h^{2}+16-8k+k^{2}=r^{2}\\-(h^{2}+64+16k+k^{2}=r^{2})\\---------------------\\h^{2}+16-8k+k^{2}-h^{2}-64-16k-k^{2}=r^{2}-r^{2}\end{array}\right.[/tex]

[tex]Simplifying: \\ \\ h^{2}+16-8k+k^{2}-h^{2}-64-16k-k^{2}=r^{2}-r^{2}\\ \\ 16-8k-64-16k=0 \\ \\ -24k-48=0 \\ \\ k=-\frac{48}{24} \\ \\ \therefore \boxed{k=-2}[/tex]

From (I):

[tex]h^2+16-8k+k^2=r^2 \\ \\ \\ For \ k=-2 \\ \\ h^2+16-8(-2)+(-2)^2=r^2 \\ \\ \therefore r^2=h^2+36 \\ \\ \\ Substituting \ k \ and \ r^2 \ into \ (III): \\ \\ h^{2}+208+16(-2)+24h+(-2)^{2}=h^2+36 \\ \\ Simplifying: \\ \\ 180+24h=36 \\ \\ 24h=36-180 \\ \\ 24h=-144 \\ \\ h=-\frac{144}{24} \\ \\ \therefore \boxed{h=-6}[/tex]

Finding the radius:

[tex]r^2=(-6)^2+36 \\ \\ r^2=36+36 \\ \\ r^2=72 \\ \\ \therefore \boxed{r=6\sqrt{2}}[/tex]

Finally, the equation of the circle is:

[tex](x-(-6))^2+(y-(-2))^2=72 \\ \\ \boxed{(x+6)^2+(y+2)^2=72}[/tex]

Answer:

[tex](x+6)^2 + (y+2)^2 = 72[/tex]

Step-by-step explanation:

We are given the following information in the question:

y intercept = 4, -8

The circle passes through the point (-12, -8)

Equation of circle:

[tex](x-h)^2 + (y-k)^2 = r^2[/tex]

where r is the radius of circle, (h,k) is the center of circle.

The circle passes through the points (0,4), (0,-8_ and (-12,-8)

Putting these points in the equation of circle we get:

[tex]1) (0-h)^2 + (4-k)^2 = r^2\\h^2 + (4-k)^2 = r^2\\2) (0-h)^2 + (-8-k)^2 = r^2\\h^2 + (-8-k)^2 = r^2\\3) (-12-h)^2 + (-8-k)^2 = r^2\\[/tex]

Now, we have three equations in three variables.

Solving the three equations, we obtain:

h = -6, k = -2, r = [tex]6\sqrt2[/tex]

Putting these values in the equation of circle:

[tex](x-(-6))^2 + (y-(-2)) = (6\sqrt{2})^2\\(x+6)^2 + (y+2)^2 = 72[/tex]

The above equation is the required equation of circle.

What is the ratio of birds to eggs? Choose 1 answer: (Choice A) 3 :4, (Choice B) 4 :3 (Choice C) 3 :5 (Choice D) D 5 :3

Answers

Answer:

1 2/3 an egg to a bird

Step-by-step explanation:

because there are 5 eggs and divide 5 by 3 you get 1 2/3 and there are 3 birds so each gets 1 2/3rds an egg

Answer:

C) 3:5

Step-by-step explanation:

The question asks for the ratio of birds to eggs. It's asking how many birds there are in comparison to the number of eggs. The key to ratios is paying attention to which is listed first.

There are 3 birds, and 5 eggs, therefore the ratio is 3:5

Which point is an x-intercept of the quadratic function f(x) = (x – 4)(x + 2)?​

Answers

Answer:

x = - 2, x = 4

Step-by-step explanation:

Given

f(x) = (x - 4)(x + 2)

To find the x- intercepts let f(x) = 0, that is

(x - 4)(x + 2) = 0 ← in standard form

Equate each factor to zero and solve for x

x - 4 = 0 ⇒ x = 4 → (4, 0 )

x + 2 = 0 ⇒ x = - 2 → (- 2, 0 )

Julio wants to calculate 200,000 300,000. When he used
his calculator to multiply, it showed the result below:
6E-10
Write the number shown on the calculator display in
standard form
OA) 60,466,176
OB) 600,000,000
OC) 6,000,000,000
OD) 60,000,000,000​

Answers

Answer: D

Just add 10 zeros behind the 6.
You get 60,000,000,000

Checking this with a calculator verifies this is the correct answer.

Answer:

D = 60,000,000,000

Step-by-step explanation:

When "E" appears on a calculator , it means exponential and it is used to denote numbers that are too big or small to appear on the calculator screen in their decimal form.

Therefore 6E-10 means 6 exponential 10 , mathematically written as  6^10

which is 60,000,000,000

c. What is the relationship between a + b and b + a?
d. What is the relationship between a - b and b - a?

Answers

Answer:

c. They are equal to each other.

d. They are the negative of each other.

Step-by-step explanation:

c. Adding c to d and d to c are the same and thus both expressions are equal. In addition, the numbers can be added in any order and will result in the same final answer. This is also known as commutative property.

d. a-b= -(b -a)

In this case, subtracting b from a is not equal to subtracting a from b. The order of terms in subtraction affects the final answer.

Find the x-intercept and the y-intercept of the graph of ax+by=c

Answers

Answer:

you need to show a picture of a graph for my answer to be acurate but I'll try.

Step-by-step explanation:

The x intercept is found by setting y = 0 in the above equation and solve for x. Hence, the x intercept is at (c/a , 0). The y intercept is found by setting x = 0 in the above equation and solve for x.

Which answer is the explicit rule for the sequence 11,8.5,6,3.5,1

Answers

Answer: 3.5−2.5n

Explanation:

To find the common difference take the end term and subtract the first term:

8.5 -11 = -2.5

Take the third term and subtract the 3rd term to verify:

6-8.5 = -2.5  check

The formula for an arithmetic sequence is:

an = a1+d(n-1)

an = 11 -2.5(n-1)

Distribute:

an = 11 -2.5n+2.5

Combine terms:

answer = 13.5 - 2.5n

Explanation: Tread more on Brainly.com - https://brainly.com/question/13244259#read more find the common difference take the end term and subtract the first term:8.5 -11 = -2.5Take the third term and subtract the 3rd term to verify:6-8.5 = -2.5  check The formula for an arithmetic sequence is: an = a1+d(n-1)an = 11 -2.5(n-1)Distribute: an = 11 -2.5n+2.5Combine terms: answer = 13.5 - 2.5nAnswer:

Answer: 3.5−2.5n

Find the next three terms of each sequence 60,52,44

Answers

Answer:

36, 28, 20

Step-by-step explanation:

To find the three terms of each sequence, simply subtract 8 from each number. For an example, you can notice the pattern by subracting 52 from 60. The answer I recieved was 8. That shows that the pattern is to subtract 8 from the following number.

Hope this helped :)

Answer:68

Step-by-step explanation:each is by 8 so add 8 onto each number to find the total

In a sample of 94 widgets, 4 were defective. How many defective widgets would you expect in a sample of 282 widgets?

Answers

Answer:

12

Step-by-step explanation: 282 divided by 94 = 3

4x3=12

Answer:

12 defective widgets

Step-by-step explanation:

Here we calculate the "experimental probability:" 4 defective widgets out of 94 widgets comes out to a probability of being defective of 4/94, which of course could be reduced.

But we can go ahead and calculate the expected number of defective widgets by mult. that 282 widgets by the probability 4/94:

282        4

------- * ------- = 12

   1         94

In this sample of 282 widgets, we could expect that 12 will be defective.

F(x) = 3x - 7 and g(x) = -2x - 6. Find (f + g)(x). Show steps.

Answers

For this, plug in x for both of the equations(so you don’t do anything because that is how it is written) and then you add them. X-13

Answer:

x - 1

Step-by-step explanation:

(f + g)(x)=f(x) + g(x)

(f + g)(x)=(3x - 7) + (-2x - 6)

(f + g)(x)= 3x - 7 - 2x + 6

(f + g)(x)= 3x - 2x - 7 + 6

(f + g)(x)= x -1

A large patio brick weighs 4 38 pounds. A small patio brick weighs 2 13 pounds.How much more does the large brick weighs

Answers

Answer:

2.25

Step-by-step explanation:

You have to subtract 2.13 from 4.38

Example: 4.38-2.13

Given: 3x + 1 = -14; Prove: x = -5

Answers

Answer:

x = -5

Step-by-step explanation:

Solve for x:

3 x + 1 = -14

Subtract 1 from both sides:

3 x + (1 - 1) = -14 - 1

1 - 1 = 0:

3 x = -14 - 1

-14 - 1 = -15:

3 x = -15

Divide both sides of 3 x = -15 by 3:

(3 x)/3 = (-15)/3

3/3 = 1:

x = (-15)/3

The gcd of -15 and 3 is 3, so (-15)/3 = (3 (-5))/(3×1) = 3/3×-5 = -5:

Answer:  x = -5

Answer:

Step-by-step explanation:

3x + 1 = -14;

substr 1 : 3x+1-1 = - 14 -1

3x = -15

divid by 3

x = -5

Noah is running a portion of a marathon at a constant speed of 6 mph. Complete the table to predict how long it would take him to run different distances at that speed and how far he would run in different time intervals.

Time in hours Miles traveled at 6mph
1.
1/2
1 1/3
1 1/2
9
4 1/2

Answers

Answer:

[tex]\begin{array}{cc}\text{Time}&\text{Distance}\\ \\1&6\\ \\\dfrac{1}{2}&3\\ \\1\dfrac{1}{3}&8\\ \\1\dfrac{1}{2}&9\\ \\9&54\\ \\4\dfrac{1}{2}&27\end{array}[/tex]

Step-by-step explanation:

Noah's running speed = 6 mph.

Use formula [tex]D=v\cdot t,[/tex] where

D is the distance,

v is the speed,

t is the time.

If [tex]t=1[/tex] hour, then [tex]D=6\cdot 1=6[/tex] miles.

If [tex]t=\dfrac{1}{2}[/tex] hour, then [tex]D=6\cdot \dfrac{1}{2}=3[/tex] miles.

If [tex]t=1\dfrac{1}{3}[/tex] hours, then [tex]D=6\cdot 1\dfrac{1}{3}=6\cdot \dfrac{4}{3}=8[/tex] miles.

If [tex]t=1\dfrac{1}{2}[/tex] hours, then [tex]D=6\cdot 1\dfrac{1}{2}=6\cdot \dfrac{3}{2}=9[/tex] miles.

If [tex]t=9[/tex] hours, then [tex]D=6\cdot 9=54[/tex] miles.

If [tex]t=4\dfrac{1}{2}[/tex] hours, then [tex]D=6\cdot 4\dfrac{1}{2}=6\cdot \dfrac{9}{2}=27[/tex] miles.

So, the table is

[tex]\begin{array}{cc}\text{Time}&\text{Distance}\\ \\1&6\\ \\\dfrac{1}{2}&3\\ \\1\dfrac{1}{3}&8\\ \\1\dfrac{1}{2}&9\\ \\9&54\\ \\4\dfrac{1}{2}&27\end{array}[/tex]

Please find attached the answers in the attached diagram

Average speed is the total distance travelled per time.

Average speed = total distance / total time

Noah's average speed is 6mph

From the above formula, the formula to determine miles run is average speed x time

Total miles he ran in 1 hour = 6 x 1 = 6 miles

Total miles he ran in 1/2 hours = 6 x 1/2 = 3 miles

Total miles he ran in 1 1/3 hours = 6 x 4/3 = 8 miles

The formula to determine total time:  total distance / average speed

Time it took Noah to run 1 1/2 miles = 3/2 ÷ 6 = 1/4 miles

Time it took Noah to run 9 miles = 9 ÷ 6 = 1 1/2 miles

Time it took Noah to run 4 1/2 miles = 9/2 ÷ 6 = 3/4 miles

Please find attached an image of the table used in answering this question

To learn more about average speed, please check: https://brainly.com/question/9834403?referrer=searchResults

The graph of an equation is shown below:

Based on the graph, which of the following represents a solution to the equation?

A) (−2,−3)

B) (3, 1)

C) (1, 3)

D) (3, 2)

Answers

The answer is (1,3). It is the only point that is in the line.

A dairy farmer ideally produces 800 gallons of milk per day. This total can fluctuate by as much as 40 gallons in either
direction. What is the maximum and minimum expected daily production?

Answers

the maximum is 840 because 800 + 40 = 840

the minimum is 760 because 800 - 40 = 760

solve the equation. 31-12n=211​

Answers

Answer:

Step-by-step explanation:

31 - 12n = 21l              Subtract 31 from both sides.

31-31-12n =211-31       Do the subtraction

-12n = 190                  Divide by -12

-12n/-12 = 190/-12

n = -15.333333

79 plus what equals 90

Answers

Answer:

11

Step-by-step explanation:

90=79+x

-79-79

_________

11=x

Mei and Anju are sitting next to each other on different horses on a carousel. Mei's horse is 3 meters from the center of the
carousel. Anju's horse is 2 meters from the center. After one rotation of the carousel, how many more meters has Mei
traveled than Anju?

Answers

Answer:

[tex]2\pi \approx 6.28\ meters[/tex]

Step-by-step explanation:

Mei's horse is 3 meters from the center of the carousel. After one rotation, Mei travelled

[tex]l_M=2\pi r=2\pi \cdot 3=6\pi\ meters[/tex]

Anju's horse is 2 meters from the center. After one rotation, Mei travelled

[tex]l_A=2\pi r=2\pi \cdot 2=4\pi\ meters[/tex]

The difference in their travelled distances is

[tex]l_M-l_A=6\pi -4\pi =2\pi \approx 6.28\ meters[/tex]

Mei travels 6.28 meters more than Anju in one rotation.

In one rotation, Mei's horse travels a distance of

2 * 3.14 * 3 = 18.84 meters.

In one rotation,

Anju's horse travels a distance of 2 * 3.14 * 2 = 12.56 meters.

Therefore, Mei travels 18.84 - 12.56 = 6.28 meters more than Anju in one rotation.

for such more question on distance

https://brainly.com/question/30395212

#SPJ3

Other Questions
Why would a person who survives a trauma resulting in massive blood loss fall victim to kidney damage or permanent renal failure? In an arithmetic sequence, the nth term an is given by the formula an=a1+(n1)d, where a1 is the first term and d is the common difference. Similarly, in a geometric sequence, the nth term is given by 1an=a1rn1,where r is the common ratio. Use these formulas to determinethe indicated term in the given sequence.The 105th term of 1/2, 1, 3/2, 2,.. ____________________ was a major reason why the United States changed more towards a mixed market economy. Question 14 options: The Civil War The American Revolution The 9/11 Attacks The Great Depressio Factor the expression: (9x)(9x)+12x+4 Which statements about ancient Greek life are shown by the story of Perseus? Check all that apply. Nights and Dragons From the memoir of author Abigail Prynne I could have given up, but I thought about my grandmother. She always told me that "people who believe that science is the answer to everything are missing out on everything else." With her words in mind, I searched some more. There were many facts that hinted that dragons may not be fictional. I noticed that cultures across the world all described dragons in similar ways. This was odd because they had no way to communicate with each other. I found dragons mentioned in more than just stories. They appeared in old legal papers, in the travel logs of Marco Polo, and in the Bible. I saw that the Chinese calendar uses a different animal each year. Dragons are included along with eleven real animals. I began to believe it was a real possibility that all of these people were talking about a creature that actually existed. Writing in a complete sentence, what is the main idea of the passage? Yesterday's World Cup final had viewing figures of 138,695,157.What is the value of the 3? Which half-reaction correctly describes an oxidation? In segment AC, the midpoint is B. If segments AC = 5x-9 and AB = 2x, what is the measure of segment AC. A graduated cylinder contains 17.5 ml of water. When a metal cube is placed onto the cylinder, its water level rises to 20.3 ml. What is the volume of the cube cm3 Consider the expression (x 6) 3xWhat is the value of the expression evaluated for x = 12? What is energy that can be released as light or thermal energy in a Reaction ________ waves need to interact with particles of either a solid, liquid, or gas to travel. Technician A says a power stroke in a modern common rail engine only uses a single injection of fuel. Tecnician B says a late-model common rail diesel has multiple injection events during a combustion cycle. Who is correct? If the initial velocity is 100 m/s at 42.8 above the horizontal and the initial height of the target is 95.5 m , how high above the ground does the collision take place? The acceleration due to gravity is 9.8 m/s 2 . X over 4 greater than or equal to negative 8 Congress is considering an increase in the minimum wage. Malinda operates an independent restaurant and is afraid this proposed increase will cause her business to become unprofitable. Malinda's concern falls into the ______________ component of the external environment. The Bonneville Salt Flats, located in Utah near the border with Nevada, not far from interstate I80, cover an area of over 30000 acres. A race car driver on the Flats first heads north for 6.71 km, then makes a sharp turn and heads southwest for 1.33 km, then makes another turn and heads east for 3.67 km. How far is she from where she started? What is X if X + R = S? the assumption that our way of thinking and acting is naturally superior to others resulting in the use of ourselves or our culture as a yardstick by which we measure what is right or desirable or normal a. Ethnocentrism b. Stereotype c. Prejudice d. Discriminationv